MEMBANGUN RESILIENSI GENERASI Z TERHADAP ADIKSI DENGAN EDUKASI PARTISIPATIF: DESKRIPSI PREFERENSI STRATEGI KOPING - Christina Lumbantoruan; David Matahari; Jessica Cecilia; Nisrina Rania (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
Generation Z faces high vulnerability to various forms of addiction, including online gambling, substance abuse, and digital dependency. This community service activity aimed to strengthen adolescents’ resilience in preventing and managing addiction risks through a participatory health education approach. The program was conducted with 137 tenth-grade students at a high school in Jakarta, consisting of three stages: interactive presentation, group discussion, and self-reflection. Participants wrote down their personal strategies for addiction prevention, which were then thematically analyzed. A total of 324 strategies were collected and categorized into seven main themes: replacing negative habits with positive ones (33.3%), increasing self-awareness and personal commitment (19.8%), building social support (13.0%), limiting access to sources of addiction (11.4%), avoiding negative influences (9.9%), strengthening spiritual aspects (7.4%), and seeking professional help (5.2%). The results showed that students preferred proactive and practical strategies, with notable differences between males and females. This activity proved effective in empowering adolescents to develop context-appropriate coping strategies, enhance self-awareness, and promote peer learning. The participatory approach can serve as a sustainable model for adolescent addiction prevention programs that are responsive to developmental needs and gender differences.